2019
DOI: 10.1142/s0218127419300313
|View full text |Cite
|
Sign up to set email alerts
|

Global Dynamics and Synchronization in a Duopoly Game with Bounded Rationality and Consumer Surplus

Abstract: Based on the oligopoly game theory, a dynamic duopoly Cournot model with bounded rationality and consumer surplus is established. On the one hand, the type and the stability of the boundary equilibrium points and the stability conditions of the Nash equilibrium point are discussed in detail. On the other hand, the potential complex dynamics of the system is demonstrated by a set of 2D bifurcation diagrams. It is found that the bifurcation diagrams have beautiful fractal structures when the adjustment speed of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…e required condition of the local asymptotic stability of Nash equilibrium point is that the eigenvalues of the corresponding Jacobian matrix are inside the unit circle. According to the Jury criterion [34], the local stability conditions of the Nash equilibrium point are as follows:…”
Section: Nash Equilibrium and Local Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…e required condition of the local asymptotic stability of Nash equilibrium point is that the eigenvalues of the corresponding Jacobian matrix are inside the unit circle. According to the Jury criterion [34], the local stability conditions of the Nash equilibrium point are as follows:…”
Section: Nash Equilibrium and Local Stabilitymentioning
confidence: 99%
“…e literature review reported above has shown that the issue of profit maximization for firms has been discussed without constraints in dynamic situation. Recently, certain games models have been investigated and have given rise to complex dynamics with some constraints, such as global analysis and multistability of Cournot duopoly market game based on consumer surpluses [34,35]. e effect of model parameters on game dynamics, coexisting attractors, and global dynamics of constrained competition games by both corporate social responsibility (CSR) and social welfare (SW) has been studied in [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…(1) e manufacturer and the retailer sell the same products from two different channels on the basis of price competition, and the marginal cost of the product is c. (2) e manufacturer and the retailer can only obtain part of market information and have limited rationality in decision-making [43]. (3) Both manufacturer and the retailer consider fairness concern in the market competition [25].…”
Section: Model Assumptionsmentioning
confidence: 99%
“…However, models à la Cournot have also been used in evolutionary settings to study, for example, reinforcement learning effects [30], implications of social and individual learning [31], impact of competing behavioral rules [32], effects of firm entry and exit on industry dynamics [33,34], and the influence of product differentiation on equilibrium stability [35]. Much recent work takes Cournot competition in dynamic settings as the steppingstone to study nonlinear behavior and equilibrium stability (e.g., [36,37,38,39]).…”
Section: Firm Competition In Evolving Attribute Spacesmentioning
confidence: 99%